maths

posted by .

SOLVE THE EQUATION FOR Z
Z divied by Z+2+i=3+i

  • maths -

    Z/(Z+2+i) = 3+i
    Z = 3Z + Zi + 6 + 2i + 3i + i^2
    Z - 3Z - iZ = i^2 + 5i + 6
    Z(-2-i) = i^2 + 5i + 6
    Z = -(i^2 + 5i + 6)/(i+2)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. ks maths

    2x - 4y = 12 3x + 2y = 10 whats the answer Do you know how to solve simultaneous equations?
  2. MATHS

    i need a lil help with this If x=2 is a root of the equation 6x^3 - px^2 - 14x + 24=0, find p,hence, solve the equation 6*(2) 3 -p*(2) 2 -14*2+24=0 6*8-p*4-14*2+24=0 48-4p-28+24=0 Can take it from here?
  3. MATH

    I NEED TO SOLVE FOR Y AND X im getting rele confused on this. ok here is the prob. x+y=5 x-2y=-4 equation 1 x+y=5 equation 2 x-2y=-4 Multiply equation 1 by -1. Add equation 1 to equation 2. The x term cancels. Solve for y. THEN, put …
  4. maths

    1x+2y=5 3x+7y=18 x= y= Multiply equation 1 by -3, add to equation 2 (which eliminates x), then solve for y. Use that value in the other equation to solve for x. Post your work if you get stuck AND explain in detail what you don't understand.
  5. Maths

    solve the following pair of simultaneous equation: (x/a)+(y/b)=1 (x/b)+(y/a)=1 can someone help please?
  6. maths

    how do i solve this equation? 2/(x+1)=1/(x-1) - (1/(2x-1)) thx Get a common denominator (x+1)(x-1)(2x-1) then, each term, multipy it out. Gather terms, solve.
  7. maths

    how would i solve the differential equation dx/dt=-kx^2 i.e. solve for x as a function of t. I've been told to rearrange the equation to yield dx/x^2=-k dt but what can and should I do now?
  8. maths

    quadratic equation solve the equation by factorization 27x^2 - 126x = 0 So x=?
  9. maths

    helo sir/madam can u help me to solve this problem solve the following simultaneous equation logx Y+logy X=5/2 xy=64
  10. maths

    1.solve the set of linear equation by matrix method.a+3b+2c=3,2a-b-3c=-8,5a+2b+c=9 solve for a,b,c 2.solve by Guassian elimination method, (a)a+2b+3c=5,3a-b+2c=8,4a-6b-4c=-2, (b)

More Similar Questions